Agriculture Cropping Pattern Change Due to Economic Standard Reforms (A Case Study on South East Hisar District, Haryana, Villages): Impacts of Changing Agricultural Cropping Patterns on Soil Fertility (Journal of Advances and Scholarly Researches in Allied Education, 2019)
By this research paper we want to explain that agriculture cropping pattern system is changing in India as well as Hisar (Haryana) year to year for growing his income standard.They are excessive use of fertilizer and ground water that is not proper applicable for his cash crops.We find that in this study area 90 farmer take mainly two crops in a year that is Paddy and Wheat.By Ch. Charan Singh Haryana Agriculture University’s Water and Soil Department lab report display to this study area testing report that study area is carrying capacity of different crops like as horticulture, floriculture, cotton, rice, wheat, maize ,barley and sugar cane etc.All farmers of this area is not aware for future productivity and harmful effect on our health. So by this research paper we want to aware to all farmers that excessive use of weedicides, pesticides and fertilizer that will change to the water composition decrease to soil fertility. Thus by this progressive farmer “s tendency that time is not far away that their cultivated land will convert in barren land